Respostas

2013-12-07T22:17:19-02:00
X^2/3-8/3=x/9           mmc de 3,9 = 9
3x^2/9-24/9=x/9
3x^2/9-24/9-x/9=0
3x^2-24-x=0
3x²-x-24=0
Δ = b² -4ac
Δ = (-1)² -4 *3 * (-24)
Δ = 1 + 288
Δ = 289
x' = (-b + √∆)/ 2a
(-(-1) + 17)/2 * 3
(1 + 17)/6
18/6= 3
x'' = (-b - √∆)/ 2a
(-(-1) - 17)/2 * 3
(1 - 17)/6
= -16/6

x²-3x/2+1/2=0            mmc de 1,2 = 2
2x²/2-3x/2+1/2=0             (1/2=0,5)
2x²-3x+0,5
Δ = b² -4ac
Δ = (-3)² -4 *2 * 0,5
Δ = 9 -4
Δ = 5
x' = (-b + √∆)/ 2a
(-(-3) + 2,23606797749979)/2 * 2
(3 + 2,23606797749979)/4
5,23606797749979/4
1,30901699437495
x'' = (-b - √∆)/ 2a
(-(-3) - 2,23606797749979)/2 * 2
(3 - 2,23606797749979)/4
0,76393202250021/4
0,190983005625053

x²/5-x/15=0              mmc de 5,15 = 15
3x²/15-x/15=0
3x²-x=0

Δ = b² -4ac
Δ = (-1)² -4 *3 * 0
Δ = 1 0
Δ = 1
x' = (-b + √∆)/ 2a
(-(-1) + 1)/2 * 3
(1 + 1)/6
2/6
x'' = (-b - √∆)/ 2a
(-(-1) - 1)/2 * 3
(1 - 1)/6
0/6= 0